STEM Integration in the Independent Curriculum for Pancasila Student Profiles in Elementary Schools - Husaen Sudrajat (Lembaga Bale Literasi, 2024)
This study aims to examine the implementation of Science, Technology, Engineering, and Mathematics (STEM) education at SDN 3 Nyerot in line with the Independent Curriculum. The research used a qualitative methodology through observation, Q&A sessions, and review of teaching documents. The results indicate that STEM education has begun to be linked to various disciplines on environmentally-focused topics, including recycling used goods, creating pamphlets on cleanliness, and calculating waste volume. This implementation encourages students to become more enthusiastic, imaginative, confident, and capable of working collaboratively in groups. However, the successful implementation of STEM at the elementary school level still requires greater support from school management and educational regulations, particularly in providing facilities and improving teacher skills. Overall, STEM teaching has great potential to support the implementation of the Independent Curriculum while developing 21st-century skills in students, such as critical thinking, creativity, synergy, and speaking skills.